PEMBERDAYAAN IBU RUMAH TANGGA MELALUI BATIK ECOPRINT - Dina Alafi Hidayatin; Latifah Anom; Ari Kuntardina; Hafidza Nash’ul Amrina; Eka Adiputra (LPPM Universitas Islam Darul 'Ulum Lamongan, 2023)
STIE. Cendekia Bojonegoro Community Service Program were conducted in Ngunut Village, Dander District, Bojonegoro Regency. Its programs include training on making eco print tote bags, training on calculating selling prices and training on product branding. The training program collaborates with PKK of Ngunut Village, Dander District, Bojonegoro Regency. The program is carried out for 21 days. Eco print training was chosen because of the abundance of teak trees in this region. Teak leaves are one of the leaves that have a strong color, so they are good as eco print materials. The program can be carried out well and welcomed by the community.